Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.pone.0207730
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A to prevent bronchopulmonary dysplasia in extremely low birth weight infants: a systematic review and meta-analysis

Abstract: BackgroundVitamin A (VA) supplementation reduces the risk of developing bronchopulmonary dysplasia (BPD). However, a previous meta-analysis showed that VA had minimal efficacy for preventing BPD in very low birth weight infants (VLBWIs).AimsTo elucidate the effects of VA supplementation for BPD prevention in extremely low birth weight infants (ELBWIs).Study designThis systematic review and meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 24 publications
1
36
0
2
Order By: Relevance
“…Though it should be noted that wide-scale studies have not shown a beneficial effect in areas of high prevalence of vitamin A deficiency [45]. Vitamin A is believed to have antioxidative properties, and has a key role in the development of bronchopulmonary dysplasia and neonatal respiratory distress syndrome [46,47]. This finding was pioneered by Hustead et al in 1984 with his work on retinol concentrations in preterm infants, in which it was discovered that neonates developing bronchopulmonary dysplasia had lower concentrations of retinol at birth [48].…”
Section: Respiratory Infectionsmentioning
confidence: 99%
“…Though it should be noted that wide-scale studies have not shown a beneficial effect in areas of high prevalence of vitamin A deficiency [45]. Vitamin A is believed to have antioxidative properties, and has a key role in the development of bronchopulmonary dysplasia and neonatal respiratory distress syndrome [46,47]. This finding was pioneered by Hustead et al in 1984 with his work on retinol concentrations in preterm infants, in which it was discovered that neonates developing bronchopulmonary dysplasia had lower concentrations of retinol at birth [48].…”
Section: Respiratory Infectionsmentioning
confidence: 99%
“…Vitamin A has been shown to play an important role in the development of bronchopulmonary dysplasia and acute respiratory distress syndrome (ARSD) [42,43]. Retinoic acid is important in the production of IL-1β and IL-1 receptor antagonists by alveolar macrophages and infiltration of pulmonary neutrophils [44], which means that both oxidative damage and the regenerative capacity of the lungs may be mediated in part by vitamin A dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Has a role in lung maturation and repair Reduces the development of BPD at 36 weeks PMA, but has no effect on long-term respiratory morbidity [130][131][132][133][134][135]…”
Section: Surfactantmentioning
confidence: 99%